1996
DOI: 10.1364/josaa.13.001981
|View full text |Cite
|
Sign up to set email alerts
|

Color memory and color constancy

Abstract: Color constancy is the perceived stability of the color of objects despite changes in the light illuminating them. An object's color is considered constant if the current perceived color is judged to be in accord with the remembered one. Thus the accuracy and precision of color memory are fundamental to understanding this classic problem. Two hypotheses of color memory are tested here: (1) the photoreceptor hypothesis, which states that the color recalled from memory reproduces the light absorbed by each type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
70
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 22 publications
7
70
0
Order By: Relevance
“…A part of Jin and Shevell's color constancy study [11] using computer simulated Munsell patches in a simple geometric arrangement the authors also report than when there was no illuminant change between the learning and testing phase (i.e. a color memory task) participants matches deviated, for both durations tested, from the original color but the nature of this variation was not systematic.…”
Section: Introductionmentioning
confidence: 97%
“…A part of Jin and Shevell's color constancy study [11] using computer simulated Munsell patches in a simple geometric arrangement the authors also report than when there was no illuminant change between the learning and testing phase (i.e. a color memory task) participants matches deviated, for both durations tested, from the original color but the nature of this variation was not systematic.…”
Section: Introductionmentioning
confidence: 97%
“…Most studies of color constancy investigate the stability of object color appearance when the illumination is varied. [1][2][3][4]6,10,11,[13][14][15][16][17][18] Although this is a natural question, it neglects an important aspect of constancy, namely, whether object color appearance is stable when the other objects in the scene are varied. [19][20][21][22][23] Computational studies indicate that it is difficult to design a visual system that adjusts to changes of illumination without introducing a dependence of color appearance on the stimulus at multiple scene locations.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative view to Zeki et al's scheme may be to agree that V4 has a special role in constancy but to ask what is the relation between constancy and other factors such as memory and judgment. Some psychophysical studies of color constancy have shown convincingly that categorical color judgments (18) and color memory (19) are fundamental to color constancy and lesion studies support this view (6). Indeed it may not make sense to think of constancy as being separate from memory: the question ''is that the same color?''…”
mentioning
confidence: 99%